Evaluation of the STAT1 mRNA expression in peripheral blood cells as a predictive marker of early pregnancy in Awassi ewes - Younis, Laith Sofian; Hatif, Saad Akram (Iraqi Journal of Science, 2024)
The primary objective of this study was to measure the expression profile of the signal transducer activator transcription 1 (STAT1) in the circulatory leukocytes of non-pregnant/pregnant ewes and test the possibility that it could be useful for detecting early pregnancy. Whole blood was collected from 20 ewes (control) and another 5 samples were taken on days (15, 25, 35, and 50). Also, blood was collected from 30 ewes on day 15 post insemination (PI) and another 10 samples were taken on days (25, 35, and 50) PI. Total RNA was isolated from peripheral blood leukocytes (PBLs), and STAT1 expression levels were determined by quantitative real-time PCR (qRT-PCR). Gene expression for STAT1 mRNA was 5.8-fold and 5.1 times higher in gravid as opposed to non-gravid ewes. The reliable cut-off point > 1.45 was established using the receiver operating characteristic (ROC) curve, and the accuracy (Acc) for detecting pregnancy was 82%, 93%, 70% and 60%, and the sensitivity (Se) was 83%, 80%, 60% and 33% and Specificity (Sp) 95% on days 15, 25, 35 and 50, respectively. The mRNA expression was lower in ewes that control non-pregnant than pregnant ewes on days 15 and 25. So The best period to detect pregnancy was 15-25 days PI.